2007
DOI: 10.1017/s002531540705521x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of Paracentrotus lividus (Echinodermata: Echinoidea) in two contrasting habitats of northern Tunisia (south-east Mediterranean)

Abstract: The reproductive strategies of the sea urchin, Paracentrotus lividus, were studied in the Bay of Tunis. Samples were collected monthly, from September 1993 to August 1995, in two sites which differ in their marine vegetation and their exposure to wave action. Histological examination demonstrated a cycle of gametogenesis with six reproductive stages and a main breeding period occurring between April and June. Gonad indices varied between sites and years, the sheltered site presenting a higher investment in rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 20 publications
6
36
0
Order By: Relevance
“…Moreover, a second relevant peak of GSI was registered in the LP zone which was demonstrated to be concomitant with a spawning event from June 2013 (Siliani et al, 2016) by histological analysis. This is consistent with observations from other areas of the Mediterranean where one or two annual spawning periods were commonly identified, regardless of the proportion of size classes shaping the population structure (Fenaux, 1968; Semroud & Kada, 1987; Pedrotti & Fenaux, 1992; Pedrotti, 1993; Semroud, 1993; Lozano et al, 1995; Fernandez & Boudouresque, 1997; López et al, 1998; Guettaf, San Martin & Francour, 2000; Leoni et al, 2003; Martínez et al, 2003; Sánchez-España, Martínez-Pita & García, 2004; Tomas, Romero & Turon, 2004; Sellem & Guillou, 2007). …”
Section: Discussionsupporting
confidence: 88%
“…Moreover, a second relevant peak of GSI was registered in the LP zone which was demonstrated to be concomitant with a spawning event from June 2013 (Siliani et al, 2016) by histological analysis. This is consistent with observations from other areas of the Mediterranean where one or two annual spawning periods were commonly identified, regardless of the proportion of size classes shaping the population structure (Fenaux, 1968; Semroud & Kada, 1987; Pedrotti & Fenaux, 1992; Pedrotti, 1993; Semroud, 1993; Lozano et al, 1995; Fernandez & Boudouresque, 1997; López et al, 1998; Guettaf, San Martin & Francour, 2000; Leoni et al, 2003; Martínez et al, 2003; Sánchez-España, Martínez-Pita & García, 2004; Tomas, Romero & Turon, 2004; Sellem & Guillou, 2007). …”
Section: Discussionsupporting
confidence: 88%
“…In population we studied the two indices are concordant though to a low level of significance. A pattern of oscillations in months with unfavorable temperatures and photoperiods (November to spring), with RI decreases not directly related to the corresponding GI, as reported by Sellem & Guillou (2007) in Tunisia, also seem to appear in our population. The lowest annual values of RI were found in this period and indicate a decrease of feeding activity that can be explained by the existence of short periods of low temperatures as these authors suggest.…”
Section: Discussionsupporting
confidence: 77%
“…In the Mediterranean Sea, Lozano et al (1995) indicated that the maturation of the gonads occurs during the winter and the main spawning during the spring or early summer, suggesting that the abundance of phytoplankton has an impact on the onset of lay. Sellem & Guillou (2007) have established the maturation period to be between April and June for populations in Tunisia, although the gonad indices also seem to vary with year and location. The hydrodynamic conditions play an important role, in such a way that in more exposed areas energy is diverted into maintenance, at least in part, at the expense of reproduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another problem associated with the GI is that causes other than reproduction can also lead to changes in gonad reserves, resulting in occasional peaks in the GI that could be interpreted incorrectly as successive spawning episodes (Byrne 1990, King et al 1994, Sellem & Guillou 2007. For instance, such peaks appeared in Sphaerechinus granularis off south Brittany (France) when the seawater temperature was abnormally low, suggesting that nutrient ABSTRACT: The gonad index is a tool widely used for studying the reproductive cycle of a large range of species, although its validity has been questioned in various scientific studies.…”
Section: Introductionmentioning
confidence: 99%